Playlist for the Apocalypse : poems - Dove, Rita (W.W. Norton & Company, 2021)
"A piercing, unflinching new volume offers necessary music for our tumultuous present, from "perhaps the best public poet we have" (Boston Globe). In her first volume of new poems in twelve years, Rita Dove investigates the vacillating moral compass guiding America's, and the world's, experiments in democracy. Whether depicting the first Jewish ghetto in sixteenth-century Venice or Black Lives Matter, this extraordinary poet never fails to connect history's grand exploits to the triumphs and tragedies of individual lives-the simmering resentment of an elevator operator, an octogenarian's exuberant mambo, the mordant humor of a philosophizing cricket. Audaciously playful yet grave, alternating poignant meditations on mortality and acerbic observations of injustice, Playlist for the Apocalypse takes us from the smallest moments of redemption to apocalyptic failures of the human soul"--